Staged residential post-acute rehabilitation for adults following acquired brain injury: A comparison of functional gains rated on the UK Functional Assessment Measure (UK FIM+FAM) and the Mayo-Portland Adaptability Inventory (MPAI-4). (19th September 2017) - Jackson, Diana; Seaman, Karla; Sharp, Kristylee; Singer, Rachel; Wagland, Janet; Turner-Stokes, Lynne
ABSTRACT: Objective : To compare the UK Functional Assessment Measure (UK FIM+FAM) and Mayo-Portland Adaptability Inventory (MPAI-4) as measures of functional change in patients with brain injury receiving a staged residential post-acute community-based rehabilitation programme. Research design: Longitudinal cohort study of consecutive admissions (N = 42) over 3 years. Methods : Patients were assessed at admission and discharge/annual review. We examined groups according to stage of independence on admission: Maximum support (stages 1 and 2: N = 17); moderate/maximum self-care/household support (stage 3: N = 15); minimal self-care and moderate household/community support (stages 4–6: N = 10). Results : Median (IQR) age: 50 (37–56) years. Male:female ratio: (71%:29%). Aetiology: stroke (50%), traumatic (36%) and other brain injuries (14%). Both tools demonstrated significant gains in overall scores and all subscales ( p < 0.01). However, the UK FIM+FAM provides more detailed evaluation of personal activities of daily living and mobility, which were most relevant in clients admitted in graduation stages 1 and 2 of the programme, whereas the MPAI-4 was more sensitive to changes in adjustment and participation for clients admitted in the later stages (4–6). Conclusions : The UK FIM+FAM and MPAI-4 provide complementary evaluation across functional tasks ranging from self-care to participation. This study supports their use for longitudinal outcome evaluation in community residential rehabilitation services that take patients at different stages of recovery.